Analisis Campur Kode pada Laporan Perjalanan Siswa Kelas VIII di SMP Negeri Gatak Tahun Ajaran 2015-2016 - Damayanti, Nicken Erma; , Prof. Dr. Abdul Ngalim, M.M, M.Hum (2016)
Trip reports are essays written by the students based on experience while traveling. The purpose of this study are to describe a form of code-mixing and Describe the factors behind the occurrence in the travel report di eighth grade students of SMP Negeri 1 Gatak the academic year 2015-2016. This type of research used in this research is qualitative research. The data in this study a word, a sentence contained in the report of students traveling mengakami code-mixing. Data collection techniques in this study using the techniques of documentation and refer to the note. Based on the data analyzed, the discovery of a form of codemixing six on a report that includes student travel, 9% word, phrase 1%, baster 1%, 1% recurrence words, idioms 1%, 2% clause.